Characteristics of suspended particulate organic matter in the southwestern Atlantic: Influence of temperature, nutrient and phytoplankton features on the stable isotope signature - Lara, Ruben Jose; Alder, Viviana Andrea; Franzosi, Claudio Atilio; Kattner, Gerhard (Journal of Marine Systems)
Surface particulate organic matter (POM) along a transect from Subantarctic coastal waters on the Argentine shelf to the Bellingshausen Sea was characterized by its organic carbon (POC) and nitrogen (PON) content and δ13C and δ15N signatures in relation to sea surface water temperature (SST), nutrients and plankton. The correlation of δ13C with SST was highly significant for the entire transect but less obvious within Subantarctic shelf ecosystems. Stable isotopes of POM varied from δ13C ~ - 12‰ and δ15N ~ 8‰ in Subantarctic shallow waters to δ13C ~ - 32‰ and δ15N ~ - 2‰ in the sector including the oceanic Subantarctic waters and the Antarctic region. In Argentine shelf waters δ13C was > - 24‰ (on average - 20.9‰) and more variable than in oceanic Subantarctic and Antarctic waters (average of - 27.6‰). High isotopic variability of POM in northern Argentine shelf waters is probably due to a pronounced nutrient gradient. There, a sharp δ13C decrease of ca. 12‰ was associated to an increase of the silicate to nitrate (Si:N) ratio to values > 0.25, and an increase of siliceous phytoplankton. Further south, Si:N ratios > 1 did not significantly affect δ13C, and the influence of the sea surface temperature (SST) was more evident. δ15N in POM of Argentine shelf waters averaged 6.3 ± 2.4‰, and the lowest δ15N values (- 1.7‰) occurred in the northern Drake Passage, where they build, together with δ13C around - 27‰, a clearly distinct pattern in the western South Atlantic. For the whole transect, SST alone accounted for 74% of the δ13C variability. A multiple regression including SST, ammonium and POC explained 83% of δ13C variance. The fit improvement by ammonium involved the nutrient-poor, regenerative system in the northernmost shallow sector and the Subantarctic shelf. δ15N showed a strong inverse relationship with the fraction of unutilized nitrate, probably due to isotopic enrichment in the nitrate pool by phytoplankton uptake. Fil: Lara, Ruben Jose. Consejo Nacional de Investigaciones Científicas y ...